Characterization and Survival of Human Infant Testicular Cells After Direct Xenotransplantation - Wang, Danyang; Hildorf, Simone; Ntemou, Elissavet; Dong, Lihua; Pors, Susanne Elisabeth; Mamsen, Linn Salto; Fedder, Jens; Hoffmann, Eva R.; Clasen-Linde, Erik; Cortes, Dina; Thorup, Jørgen; Andersen, Claus Yding (Frontiers in Endocrinology, 2022)
Background: Cryopreservation of prepubertal testicular tissue preserves spermatogonial stem cells (SSCs) that may be used to restore fertility in men at risk of infertility due to gonadotoxic treatments for either a malignant or non-malignant disease. Spermatogonial stem cell-based transplantation is a promising fertility restoration technique. Previously, we performed xenotransplantation of propagated SSCs from prepubertal testis and found human SSCs colonies within the recipient testes six weeks post-transplantation. In order to avoid the propagation step of SSCs in vitro that may cause genetic and epigenetic changes, we performed direct injection of single-cell suspension in this study, which potentially may be safer and easier to be applied in future clinical applications. Methods: Testis biopsies were obtained from 11 infant boys (median age 1.3 years, range 0.5-3.5) with cryptorchidism. Following enzymatic digestion, dissociated single-cell suspensions were prelabeled with green fluorescent dye and directly transplanted into seminiferous tubules of busulfan-treated mice. Six to nine weeks post-transplantation, the presence of gonocytes and SSCs was determined by whole-mount immunofluorescence for a number of germ cell markers (MAGEA, GAGE, UCHL1, SALL4, UTF1, and LIN28), somatic cell markers (SOX9, CYP17A1). Results: Following xenotransplantation human infant germ cells, consisting of gonocytes and SSCs, were shown to settle on the basal membrane of the recipient seminiferous tubules and form SSC colonies with expression of MAGEA, GAGE, UCHL1, SALL4, UTF1, and LIN28. The colonization efficiency was approximately 6%. No human Sertoli cells were detected in the recipient mouse testes. Conclusion: Xenotransplantation, without in vitro propagation, of testicular cell suspensions from infant boys with cryptorchidism resulted in colonization of mouse seminiferous tubules six to nine weeks post-transplantation. Spermatogonial stem cell-based transplantation could be a therapeutic treatment for infertility of prepubertal boys with cryptorchidism and boys diagnosed with cancer. However, more studies are required to investigate whether the low number of the transplanted SSC is sufficient to secure the presence of sperm in the ejaculate of those patients over time.